Tata Kelola Pengelolaan Sampah Berbasis Bank Sampah - Prakasdi, Rika Galeindra; Septiawan, Catur; Ardiansyah, Ardiansyah (Journal of Public Health Education, 2024)
Introduction: The projection is that by 2050, waste generation will reach 3.40 billion tons, assuming population growth is more than doubled in the same period Objectives: To find out the governance of waste management based on the main Garbage Bank Rumah Harum Depok in 2023. Method: This research uses a qualitative approach to analyze waste management based on the Rumah Harum Depok Waste Bank in 2023. Researchers use supporting instruments in the form of interview guides, related documents, and cellphones (cameras and recorders). There were 3 informants in this study. Data analysis in this research includes data reduction, data presentation, and concluding. Results: The input factors for the Rumah Harum Main Waste Bank are the recommendations of the Minister of Environment and Forestry Regulation No. 14 of 2021 concerning Waste Management in Waste Banks. Process factors regarding the institutional structure of the Rumah Harum Main Waste Bank are not to the recommendations of the Minister of Environment and Forestry Regulation No. 14 of 2021 concerning Waste Management at Waste Banks. Conclusion: There are almost the same details of tasks between the institutional structure of Rumah Harum Waste Bank and the institutional structure of the Minister of Environment and Forestry Regulation No. 14 of 2021.